2010
DOI: 10.1021/op100118e
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Impurities: From Structural Alerts to Qualification

Abstract: The presence of an in cerebro structural alert in a potential or actual impurity, most likely arising as a byproduct or carriedover reagent or starting material, in a drug substance or drug product is merely an indication that the compound may be a DNAreactive genotoxin. The correlation between structural alerts for direct or indirect electrophilic characteristics and relevant biological activity is highly imperfect. For virtually all actual or potential impurities that are structurally alerting there is likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 85 publications
2
96
0
Order By: Relevance
“…Hydralazine (1-hydrazinylphthalazine) and its hydrochloride salt are Ames-positive. In another study, 20 hydrazine-derivatives were found to induce a direct DNA damage in Escherichia coli and 16 of them (80%) were Ames positive as well (Flora et al, 1984; Agency for Toxic Substance and Disease Registry, 1997;Snodin, 2010).…”
Section: Genotoxicity Profilementioning
confidence: 98%
See 4 more Smart Citations
“…Hydralazine (1-hydrazinylphthalazine) and its hydrochloride salt are Ames-positive. In another study, 20 hydrazine-derivatives were found to induce a direct DNA damage in Escherichia coli and 16 of them (80%) were Ames positive as well (Flora et al, 1984; Agency for Toxic Substance and Disease Registry, 1997;Snodin, 2010).…”
Section: Genotoxicity Profilementioning
confidence: 98%
“…The SN1 mechanism leads to O-alkylation (O-6-methylguanine) which is mutagenic but not clastogenic, whereas the SN2 mechanism leads to N-methylation which is clastogenic and not mutagenic. In this group, it seems that bromo compounds are more reactive as compared to chloro compounds (Sobol et al, 2007;Snodin, 2010). Various tests have been performed to study DNA damage and mutation in alkyl halides.…”
Section: Genotoxicity Profilementioning
confidence: 99%
See 3 more Smart Citations